Precise tuning of bacterial translation initiation by non-equilibrium 5′-UTR unfolding observed in single mRNAs. Issue 15 (27th July 2022) - Ray, Sujay; Dandpat, Shiba S; Chatterjee, Surajit; Walter, Nils G
Abstract: Noncoding, structured 5′-untranslated regions (5′-UTRs) of bacterial messenger RNAs (mRNAs) can control translation efficiency by forming structures that either recruit or repel the ribosome. Here we exploit a 5′-UTR embedded preQ1 -sensing, pseudoknotted translational riboswitch to probe how binding of a small ligand controls recruitment of the bacterial ribosome to the partially overlapping Shine-Dalgarno (SD) sequence. Combining single-molecule fluorescence microscopy with mutational analyses, we find that the stability of 30S ribosomal subunit binding is inversely correlated with the free energy needed to unfold the 5′-UTR during mRNA accommodation into the mRNA binding cleft. Ligand binding to the riboswitch stabilizes the structure to both antagonize 30S recruitment and accelerate 30S dissociation. Proximity of the 5′-UTR and stability of the SD:anti-SD interaction both play important roles in modulating the initial 30S-mRNA interaction. Finally, depletion of small ribosomal subunit protein S1, known to help resolve structured 5′-UTRs, further increases the energetic penalty for mRNA accommodation. The resulting model of rapid standby site exploration followed by gated non-equilibrium unfolding of the 5′-UTR during accommodation provides a mechanistic understanding of how translation efficiency is governed by riboswitches and other dynamic structure motifs embedded upstream of the translation initiation site of bacterial mRNAs.